2009
DOI: 10.1348/096317908x342909
|View full text |Cite
|
Sign up to set email alerts
|

What's the difference? Insider perspectives on the importance, content, and meaning of interpersonal differences

Abstract: This study presents a new approach to examine how team members experience interpersonal differences. This approach offers a way to examine how team members experience their differences with specific other individuals, and how these differences are related to the amount of perceived conflict with these individuals in an organizational context. Data from a non-profit governmental institution in The Netherlands were analysed, including 80 participants from 15 diverse teams. Five types of differences were salient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The participants were asked to write down three features that in their view differentiated group members from each other. In Oosterhof et al (2009), participants also reported an average of three differences per relationship. For each feature, participants were asked how strong they perceived this difference in the group to be (from 1 = not strong to 5 = very strong).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were asked to write down three features that in their view differentiated group members from each other. In Oosterhof et al (2009), participants also reported an average of three differences per relationship. For each feature, participants were asked how strong they perceived this difference in the group to be (from 1 = not strong to 5 = very strong).…”
Section: Methodsmentioning
confidence: 99%
“…We are aware of one other study that follows these notions and that investigated perceived social categories without restraining participants to a set of predetermined categories. Oosterhof, van der Vegt, van de Vliert, Sanders, and Kiers (2009) asked 80 members of different teams of a nonprofit organization about attributes that they perceive as differentiating them from their colleagues. In response, participants named 497 dissimilarity attributes-an average of almost three attributes per colleague.…”
Section: Measuring Social Categorizationsmentioning
confidence: 99%
“…Meyer, Shemla, Wegge, & Li, 2015). This type of perceived diversity assesses the global perception of diversity across the limitless dimensions of diversity that exist in any team (Oosterhof, van der Vegt, van de Vliert, Sanders & Kiers, 2009). An example use of this type can be found in a paper by Jehn and Bezrukova (2010) who asked participants to rate the degree to which their team was split into subgroups, broke into alliances, and divided into subsets of individuals.…”
Section: Different Forms Of Perceived Diversity As Mediatorsmentioning
confidence: 99%
“…Measuring objective levels of diversity (based on, for example, team members' age or educational specializations) is problematic insofar as it presupposes that such characteristics are all salient to team members. Indeed, it has been shown that different aspects of diversity can be salient for different people (see Oosterhof, van der Vegt, van de Vliert, Sanders, & Kiers, 2009). In fact, Harrison, Newman, and Roth (2006) advised researchers to conceptualize an attribute of interest at a high level of abstraction when investigating work behavior through attitudes of team members.…”
Section: Perceived Diversitymentioning
confidence: 99%